Markups and Concentration in South African Manufacturing Sectors: An Analysis with Administrative Data. (3rd November 2017) - Fedderke, Johannes; Obikili, Nonso; Viegi, Nicola
Abstract: This paper uses newly available firm‐level tax data to evaluate the market structure in South African manufacturing sectors in the period 2010‐2012. To describe the market structure, we compute markups for South African manufacturing firms and concentration indexes for 4‐digit manufacturing sectors. We find both significant markups and significant concentration across most sectors. We compare computed markups and concentration with early estimates in South Africa and with other international benchmark countries. We then examine the market structure based on the concentration, firms size and entry and exit dynamics to rule out some potential explanations for relatively high markups. We find that the relationships are not monotonic and point to the importance of specific barriers to entry in explaining the relationship between these three characteristics.